(untitled) (Praxis Educativa, 2026)
Writing at classes in secondary school is an usual practice. In a scene that is frequently repeated, students copy from the blackboard, answer questionaries and fill evaluations. But, what meanings do these writigs assume? Not all writing practices lead to knowledge building, but for this to occur certain didactic conditions are required. In this article, we analize writings produced by fifth-year high school students in the subject Sociology, during the development of a didactic research. We aim to compare two different writing situations, one at the begging of the didactic sequence and the other at the end. This article reports findings on how students writings gain in complexity, as a result of them participating in learning activities and in exchanges with profesor and classmates. We focus on how students approach to analysis perspective of Sociology.